A review on MXene and its' composites for electromagnetic interference (EMI) shielding applications. (May 2023) - Verma, Ritesh; Thakur, Preeti; Chauhan, Ankush; Jasrotia, Rohit; Thakur, Atul
Abstract: The MXene family is the most rapidly expanding group of 2D materials due to its properties such as high conductivity, greater water dispersibility, surface chemical tunability, easy processability, and exceptional thermal stability. MXenes also show effective electromagnetic interference (EMI) shielding; however, MXenes' EMI shielding properties may be further enhanced by combining it with other materials to create a variety of composites, such as those with polymers, fibres, carbon derivatives, nanoferrites, and metal-organic frameworks (MOF). In this review, the parameters like shielding effectiveness (SE), absolute shielding effectiveness (SSE/t), specific shielding effectiveness (SSE/ρ), electrical conductivity (σ) are discussed thoroughly. The shielding components of total attenuation of EM waves ( S E T ) such as attenuation due to absorption ( S E A ), attenuation due to reflection ( S E R ) and attenuation due to multiple reflections ( S E M ) are discussed with the best possible mechanism. The value is critical in determining the effectiveness of shielding material. S E T < 10 dB means no shielding, S E T = 10–30 dB indicates the minimum effective range of shielding and S E T ≥ 30 dB signifies the best efficiency of a shielding material for industrial applications. The discussion made in this review will be helpful to researchers working in the field of defence technology, high-frequency devices, and microwave applications. The discussion could also be used to synthesise and evaluate the performance of novel materials for EMI shielding using MXenes. Graphical abstract: Electromagnetic interference (EMI) shielding mechanism of MXene composites. Image 1 Highlights: MXene is one of the emerging materials with EMI shielding efficiency. MXene composites with polymers, carbon, ferrites, cotton fabric show significant improvement in EMI shielding parameter. MXene composites based shielding materials are light-weight, flexible, provides large surface area, and high conductivity. Total Shielding effectiveness depends on absorption, reflection, and internal multiple reflections. Improvement of absorption and multiple reflections improve the shielding efficiency of MXene composite.